2011
DOI: 10.1016/j.psychsport.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Territorial gain dynamics regulates success in attacking sub-phases of team sports

Abstract: a b s t r a c tBackground and objective: Field invasion games, such as rugby union, can be conceptualised as dynamic social systems in which the agents continuously interact to contest ball possession and territorial gain. Accordingly, this study aimed to identify the collective system dynamics of rugby union phases-of-play near the try line by investigating whether ball displacement trajectory on the playing field provides insights on successful team performance. Methods: Five rugby union matches were videota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…In the current state-of-the-art, only a few papers have analysed the variability of displacement of football players [13][14][15]. All these studies focused on the variability within each sub-phase (e.g., 1 vs. 1 player, 2 vs. 2 players) without considering the full match dynamics (e.g., 11-a-side game).…”
Section: Variability Analysis In Sportmentioning
confidence: 99%
“…In the current state-of-the-art, only a few papers have analysed the variability of displacement of football players [13][14][15]. All these studies focused on the variability within each sub-phase (e.g., 1 vs. 1 player, 2 vs. 2 players) without considering the full match dynamics (e.g., 11-a-side game).…”
Section: Variability Analysis In Sportmentioning
confidence: 99%
“…They found that all teams exhibit a chaotic pattern in their performance over time, and that the top performing teams displayed a low-dimensional chaotic pattern. Another study with rugby teams, by Correia et al (2011) found that the effectiveness of attacking teams is predicted by the variability of their movements and by entropy levels in players' movements. These studies support the idea of healthy variability at different levels of analysis (i.e., performance at team level and movements at members level).…”
Section: Methodsmentioning
confidence: 99%
“… 4 [ 21 , 87 , 99 , 100 ] 15 [ 13 15 , 20 , 51 , 55 58 , 75 , 86 , 95 98 ] 2 [ 18 , 108 ] Performance—how Complete season/tournament? 5 [ 53 , 54 , 65 , 102 , 109 ] 12 [ 11 , 12 , 16 , 17 , 19 , 62 , 72 , 76 , 88 , 101 , 103 , 104 ] Is the research from a one-off tournament(s)? 2 [ 88 , 109 ] 15 [ 11 , 12 , 16 , 17 , 19 , 53 , 54 , 62 , 65 , 72 , 76 , 101 – …”
Section: Main Textmentioning
confidence: 99%
“…Video analysis research in rugby union frequently includes what studies that identify key events (for example, number of tackles in a match) to how studies that describe key events (for example, tackle technique relates to injury). Furthermore, the scope of these studies range from the description of in-depth case studies [ 10 12 ] to the broad analysis of commercial data bases [ 13 15 ]; and from studies that apply sophisticated statistical modelling that accounts for context [ 16 18 ] to studies that only report on the frequencies of events [ 19 21 ]. The sizes and types of samples used in these studies also vary considerably, a similar finding to that in Association Football (for a review: see Mackenzie and Cushion, 2013 [ 22 ]).…”
Section: Introductionmentioning
confidence: 99%